Peran Kepala Sekolah dalam Meningkatkan Mutu Sumber Daya Manusia : The Role of School Principals in Improving the Quality of Human Resources - Munawwarah, Faiqatul; Jannah, Faridatul; Nurhadi, Ali (Thawalib: Jurnal Kependidikan Islam, 2024)
The purpose of this study is to explain and describe the role of the principal in improving the quality of human resources at Al-Ghafur Vocational High School in Sumenep. The research method used is qualitative through a case study. Data collection techniques include interviews, observations, and documentation. The results of the study show that the principal's strategy in improving the quality of human resources includes the design and development of a curriculum that meets the needs of students, with a primary focus on HR management. The goal is for all school members to have a high spirit to advance the educational institution. Other strategic steps include regular performance monitoring and evaluation, as well as staff training and skills development. The principal also strives to build good relationships with the community through meetings with students' guardians, social activities, and school events. As an educational manager, the principal focuses on improving HR quality through regular planning, organizing, directing, coordinating, and supervising. Factors such as effective leadership, a supportive organizational culture, clear policy implementation, technology development, and HR training also play important roles in improving HR quality.